Trichomicosis pubis: black variety. Issue 5 (October 1994) - Neri, I; Frassetto, A; Pasquinelli, G; Patrizi, A
Abstract : A case of a 25 year old man with the black variety of trichomicosis pubis is presented on account of its extreme rareity. Scanning electron microscopy confirms that trichomicosis pubis is caused by bacterial colonisation of the pubic hair and shows that bacteria are able to penetrate cuticular horny cells directly through their free plasma membrane.